Chemical Immobilization and Conversion of Active Polysulfides Directly by Copper Current Collector: A New Approach to Enabling Stable Room‐Temperature Li‐S and Na‐S Batteries. Issue 22 (16th May 2018) - Li, Peirong; Ma, Lu; Wu, Tianpin; Ye, Hualin; Zhou, Junhua; Zhao, Feipeng; Han, Na; Wang, Yeyun; Wu, Yunling; Li, Yanguang; Lu, Jun
Abstract: Room‐temperature Li/Na‐S batteries are promising energy storage solutions, but unfortunately suffer from serious cycling problems rooted in their polysulfide intermediates. The conventional strategy to tackle this issue is to design host materials for trapping polysulfides via weak physical confinement and interfacial chemical interactions. Even though beneficial, their capability for the polysulfide immobilization is still limited. Herein, the unique sulfiphilic nature of metallic Cu is revisited. Upon the exposure to polysulfide in aqueous or aprotic solution, the surface sulfidization rapidly takes place, resulting in the formation of Cu2 S nanoflake arrays with tunable texture. When the sulfidized Cu current collector is directly used as the sulfur‐equivalent cathode, it enables high‐performance Li/Na‐S batteries at room temperature with reasonable high sulfur loading. Specific capacities up to ≈1200 mAh g −1 for Li‐S and ≈400 mAh g −1 for Na‐S are measured when normalized to the amount of equivalent sulfur, and can be readily sustained for >1000 cycles. Abstract : Metallic Cu foams can be used as the working electrode to trap polysulfides from the electrolyte, leading to the formation of Cu2 S nanoflake arrays with tunable texture and thickness. The thus sulfidized Cu foams are investigated as the sulfur‐equivalent cathode to enable high‐performance Li‐ or Na‐S batteries at room temperature.